Analisis Kualitas Situs Web Batampos Menggunakan Metode WebQual 4.0 - Yodi Yodi (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Batampos is the largest daily newspaper in riau islands spread from batam island, tanjung pinang, natuna even to singapore and malaysia. Along with the development of information technology and communications batampos also make a web site batampos newspaper to continue to provide convenience for its readers. The purpose of this research is to know how far the quality of Batampos website based on end user perception so that batampos site can increase the number of visitors and competition with similar website. This research method uses WebQual 4.0 that focuses on three main components namely usability, information quality and service interaction quality. Data collection method using primary data in the form of questionnaires distributed online amounted to 200 responden. Data analysis techniques using descriptive analysis with statistical calculations with multiple linear regression analysis using SPSS 22. Based on data processing can be seen that the user perception of Quality Usability, Information Quality, Service Interaction Quality independently have a positive and significant impact on user satisfaction